Babad Kangjeng Ratu Kancana 1936: Representasi Nilai Tembang Macapat Sinom dalam Tradisional Jawa Kuna - Yuniar, Dennis Putri; Amiq; Azizah, Mutiatul Affita Nur (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2025)
This study examines the representation of the values of Macapat Sinom songs in Babad Kangjeng Ratu Kancana 1936 by Sastrasumarta, as part of ancient Javanese historical literature that faces the threat of extinction due to the lack of oral transmission and digitization. The purpose of this study is to analyze the representation of Sinom song values through the structure of the babad text and to reveal the meaning of its cultural values as the social identity of pre-modern Javanese society. The method used is qualitative text analysis with triangulation of sources, including open coding, thematic grouping (moral idealism, social ethics, cultural identity), and interpretation through Tajfel-Turner's Social Identity Theory (SIT), based on digital texts from Sastra.org. The results of the study show that the Sinom III pupuh represents the values of village-priyayi harmony, brata loyalty, and susila ethics through a 15-verse narrative structure: introduction of characters (stanzas 1-5), development of the Rara Beruk family (6-10), and moral advice (11-15), which form the collective identity of Ancient Java through social categorization, identification of pious characters, and hierarchical comparisons. This song serves as a medium for cultural education, bridging nrimo ing pandum and bagya for the revitalization of traditional values in the era of globalization.